Self and Peer Assessment Based on Storytelling: Implementation on Islamic Education Learning - Rahmah, Nihayatur; Ummah, Fiena Saadatul; Hadi, Ahmad Safi’ie (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to find out the techniques of self-assessment and peer assessment through the storytelling method as well as the benefits of the storytelling-based self-assessment and friend process for students and teachers. This article uses qualitative research methods to explore a deep understanding of self-assessment and peer judgment based on storytelling. Data were collected through self-assessment and in-depth interviews that allowed researchers to explore the rich perspectives of the participants directly. Data analysis is carried out thematically, by highlighting patterns that emerge from the data and providing a holistic interpretation of the phenomenon being studied. The results of the study show that self-assessment and peer assessment using storytelling in Islamic religious education learning can be done in several steps, namely determining the competencies or aspects to be assessed, determining the assessment criteria to be used, formulating an assessment format, and in the form of assessment guidelines, checklists, or assessment scales, asking students to do self-assessments, teachers reviewing evaluation samples at random, encourage students to always conduct careful and objective self-assessments. The second technique can be done by providing some narrative questions. In this case, students will be asked to share the results of their assessment in front of teachers and friends in turn